A new approach for improving epothilone B yield in Sorangium cellulosum by the introduction of vgb epoF genes. (1st May 2016) - Ye, Wei; Zhang, Weimin; Chen, Yuchan; Li, Haohua; Li, Saini; Pan, Qingling; Tan, Guohui; Liu, Taomei
Abstract: Epothilone B has drawn great attention due to its much stronger anticancer activity and weaker side effects compared with taxol. The relative low yield of epothilone B limited its application. In this study, we report the successful introduction of the vgb gene and the epoF gene into Sorangium cellulosum So ce M4 by electroporation for the first time, which was demonstrated by Southern blot analysis. Results of qRT-PCR, SDS-PAGE and western blot analysis confirmed the transcription and expression of the vgb and epoF genes. LC–MS results showed that the epothilones B, A yields were improved and epothilones D, C yields were decreased. The yields of epothilone B were improved by 57.9 ± 0.3, 62.7 ± 0.8 and 122.4 ± 0.7 % through the introduction of vgb gene, epoF gene and both genes into strain So ce M4, respectively. Our study provides a new approach for improving epothilone B yield in S. cellulosum.